Empowerment in an ecovillage: Unveiling the role of power relations in social practices. Issue 5 (20th October 2021) - Mafle Ferreira Duarte, Luiz Guilherme; Sahakian, Marlyne; Ferreira Neto, João Leite
ABSTRACT: Living in an ecovillage requires that people reinvent everyday practices. It involves new forms of production, consumption, social organization, and subjective constitution, aiming toward the normative goal of achieving greater "sustainability." Based on ethnographic research in Western Switzerland, this paper focuses on uncovering the nexus of power relations, social practices, and empowerment in daily life in an ecovillage. We find that power relations and social practices are intertwined, leading to different outcomes regarding empowerment. Procedures, understandings, and forms of engagement constitute social practices; however, power relations can either cause or constrain the rearrangement of practices toward different forms of individual and community empowerment, whereby some practices "orchestrate" others.